Perspectives to mitigate payer uncertainty in health technology assessment of novel oncology drugs. Issue 1 (1st January 2019) - Solà-Morales, Oriol; Volmer, Timm; Mantovani, Lorenzo
ABSTRACT: Reimbursement decisions on new oncology drugs are now often made while uncertainty remains about a drug's risk–benefit profile. One consequence of this is a delay in patient access to valuable new medicines. We share our perspectives on strategies to mitigate sources of uncertainty in the health technology assessment process. These include flexible approaches for evaluating the additional benefit, such as better use of surrogate endpoints and health-related quality of life data, and renewed research efforts to define the optimal target population and generate real-world evidence post-authorisation.